2019
DOI: 10.1186/s12884-019-2227-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neonatal mortality in Neonatal intensive care unit at referral Hospital in Southern Ethiopia: a retrospective cohort study

Abstract: Background The first one month of life; the neonatal period is the most risky time for child survival. In Ethiopia, neonatal mortality is unacceptably high, and the trend in reduction is slower as compared to infant and child mortality. The magnitude and associated factors of neonatal mortality in a tertiary care facility were not well documented. Therefore, the aim of this study was to determine neonatal mortality and predictors among neonates admitted to neonatal intensive care unit of Wolaita S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
112
9
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 18 publications
33
112
9
5
Order By: Relevance
“…Preterm and low birth weight babies were more likely to be prone to complications such as hypothermia, infections, and birth asphyxia (resulting in tissue hypoxia and multi-organ failure). Therefore, provisions of quality neonatal care, including quality resuscitation, thermal care, and appropriate feeding, are important to avert some of these factors [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm and low birth weight babies were more likely to be prone to complications such as hypothermia, infections, and birth asphyxia (resulting in tissue hypoxia and multi-organ failure). Therefore, provisions of quality neonatal care, including quality resuscitation, thermal care, and appropriate feeding, are important to avert some of these factors [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…All studies were published from 2012 to 2019. Six of the studies identified employed hospital-based cohort designs [24][25][26][27][28][29]; the remaining four applied cross-sectional designs [30,31] ( Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The findings of these uneven studies documented that there was a great variability in the prevalence of neonatal mortality across the regions of the country. Concerning predictors, these studies revealed that different maternal, neonatal and health service related factors influenced neonatal mortality; maternal residency [ [16,17]], history of antenatal, gestational age ,neonatal sepsis, RDS, asphyxia were some of the factors associated with neonatal mortality [18,19].Globally, there are different policies, strategies, and programs which work on prevention and care of neonate [20,21]. However, it is sustained as the most cause of under-five mortality worldwide [11,[22][23][24][25].Despite different strategies, health policies (like HSDP IV 2010-2015) and interventions were implemented to prevent and care neonatal death, the rate of neonatal mortality is high.…”
Section: Introductionmentioning
confidence: 99%